Accounting before Accountability - Yeow Meng Thum (Universidad de Navarra, 2009)
In this article, we will review several issues relating to the definition of "adequate yearly progress" (AYP), and its measurement, and offer some reasons why it may be prudent to separate the definition and measurement of AYP from its use in accountability. The design of accountability system includes general prescriptions about what data are relevant, policy questions that will guide the formulation of progress and productivity indicators based on students' longitudinal test scores, and procedures for using the resulting indicators in accountability.